2009
DOI: 10.1097/ncq.0b013e31818f557c
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Recently Discharged Patients on Hospital Fall-Prevention Programs

Abstract: The aim of this exploratory study was to understand the opinions and observations of recently discharged senior patients concerning the fall-prevention education received during their most recent hospitalization. The focus was on the extrinsic risk factors for falls. This project was conducted in a Michigan home care agency. Participants had to be Medicare home care patients, discharged from the affiliated hospital within 30 days, 65 years or older, and alert. Practical implications that might lead to fewer fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…En los artículos encontrados, todas estas medidas han producido una reducción significativa de las caídas (13,15,(47)(48)(49)(50)(51)(52).…”
Section: Resultsunclassified
“…En los artículos encontrados, todas estas medidas han producido una reducción significativa de las caídas (13,15,(47)(48)(49)(50)(51)(52).…”
Section: Resultsunclassified
“…Patients 65 years and older who were recently discharged from a United States hospital expressed a need for nurses to give and repeat directives about fall prevention 1. These patients found that when the nurse left a brochure on the topic, but did not provide any (or limited) verbal explanations about the content or importance of the information, the patient felt that the information was insufficient 1.…”
Section: Introductionmentioning
confidence: 99%
“…These patients found that when the nurse left a brochure on the topic, but did not provide any (or limited) verbal explanations about the content or importance of the information, the patient felt that the information was insufficient 1. Patients are entitled to receive quality fall prevention care tailored to their risk for falling, and such patient centeredness could lead to safe hospital stays 2.…”
Section: Introductionmentioning
confidence: 99%
“…24 Nurses identified cognitive impairment, Alzheimer's, disorientation, patient inability to follow safety instruction, and imbalance/gait problems as the most frequently observed risk factors for patient falls. 25 A well designed education program with visual cues that engaged the patient and more frequent repetition of fall prevention messages from nurses were recommended improvements.…”
Section: Factors Related To Risk Of Falling When Hospitalizedmentioning
confidence: 99%
“…22,23 Environmental risk factors included a higher percentage of falls occurring in the evening hours, lack of access to ambulatory assistive devices, absence of clear pathways in the hospital room, failing to keep the bed height in the low position, failure to apply brakes on the bed, lack of proper footwear, good lighting, and prompt call bell responses by nursing personnel. 18,24,25 Insights from patients and caregivers on fall prevention…”
Section: Factors Related To Risk Of Falling When Hospitalizedmentioning
confidence: 99%